Modul Ajar Berbasis Merdeka Belajar di SD Negeri 2 Manna - Nurhayati, Tiara; Dhori, Muhammad (Lembaga Intelektual Muda (LIM) Maluku, 2025)
The purpose of this research is to increase learning resources and make it easier for teachers to carry out learning, both in closed (in the classroom) and open classes (for example online learning or blended learning). the research approach uses a qualitative descriptive research approach and type. This research method is qualitative with the technique used content (Content analysis) is a method on dynamic things that examine and describe the main elements guided by content elements. The result of the research is that this teaching module is very effective in terms of supporting a more structured learning process, as well as ensuring that the learning process can run more purposefully, according to the specified learning and assessment guidelines. The development of teaching modules is very relevant to the Merdeka Curriculum, which is currently implemented at the elementary school, secondary school, and tertiary levels. The Merdeka Curriculum emphasizes a more flexible approach that supports students to learn according to their needs, and develop competencies and characters more holistically and strengthen the quality of quality education in Indonesia. Teachers develop teaching modules first, then the learning process in the classroom begins. The conclusion of this article is that the use of teaching modules is to minimize the burden on teachers when providing material. Teachers can have a good time allocation into tutorials and help students in learning mechanisms